ENVIRONMENTAL COMPETENCE: THEORETICAL AND METHODOLOGICAL APPROACHES - Mamajonov Shukhratjon Askarovich (EPRA International Journal of Research and Development (IJRD), 2022)
In the conditions of modernization of modern education, the competence-based approach is one of the leading principles for determining the content of education and ways of organizing it. Environmental competence is an important area of modern educational systems at different levels - school and university - and acts as both a general cultural and professional component. This article analyzes the essence of environmental competence and environmental competence, their relationship in the system of categories of environmental psychology and pedagogy. The structure and content of environmental competence at the level of general secondary education are proposed.